Myt1 overexpression mediates resistance to cell cycle and DNA damage checkpoint kinase inhibitors - Sokhi, Sargun; Lewis, Cody W.; Bukhari, Amirali B.; Hadfield, Joanne; Xiao, Edric J.; Fung, Jeremy; Yoon, Yea Jin; Hsu, Wen-Hsin; Gamper, Armin M.; Chan, Gordon K. (Frontiers in Cell and Developmental Biology, 2023)
Cell cycle checkpoint kinases serve as important therapeutic targets for various cancers. When they are inhibited by small molecules, checkpoint abrogation can induce cell death or further sensitize cancer cells to other genotoxic therapies. Particularly aberrant Cdk1 activation at the G2/M checkpoint by kinase inhibitors causing unscheduled mitotic entry and mitotic arrest was found to lead to DNA damage and cell death selectively in cancer cells. Promising drugs inhibiting kinases like Wee1 (Adavosertib), Wee1+Myt1 (PD166285), ATR (AZD6738) and Chk1 (UCN-01) have been developed, but clinical data has shown variable efficacy for them with poorly understood mechanisms of resistance. Our lab recently identified Myt1 as a predictive biomarker of acquired resistance to the Wee1 kinase inhibitor, Adavosertib. Here, we investigate the role of Myt1 overexpression in promoting resistance to inhibitors (PD166285, UCN-01 and AZD6738) of other kinases regulating cell cycle progression. We demonstrate that